PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VIII SMPN 1 PARIAMAN - Misra Delina (Jurnal Edukasi dan Penelitian Matematika, 2019)
The ability to solve mathematical problems is an important aspect that needs to be achived in mathematics learning. In fact, learning activities at SMPN 1 Pariaman was not optimal yet in facilitating students to improve those aspects. Students were difficult to solve math problems especially the problems were in essay tes, besides they were not involved actively in mathematics learning activities. One of way to solve this problem was by applying the Problem Based Learning (PBL) model. The type of the research was a quasi-experimental with Randomize Control Group Only Design. The results of this research indicates that students’ mathematical problem solving ability who studied with PBL model is better than who studied with conventional learning. This result is proved by hypotheses test result that P-Value=0,000 < Keyword – conventional learning, mathematical problem solving ability, PBL model